Analysis of Student’s Metacognitive Errors in Working on PISA-Like Math Problem on Number Content - Hanayuki Alya; Jenny Nurika Aryani; Aliyyah Salsabila; Ratu Ilma Indra Putri; Elsa Susanti; Ruth Helen Simarmata (Southeast Asian Mathematics Education Journal, 2025)
This study aims to analyze the forms of metacognitive errors made by junior high school students in solving questions developed by the Programme for International Student Assessment (PISA) on number content. Metacognitive skills are part of a higher-order thinking process that includes awareness and control of one's own thinking process, including strategy planning, monitoring implementation, and evaluating results. In the context of PISA-like math problem that require contextual and complex problem solving, these skills are crucial. This study employed a qualitative approach using a case study design. The research subjects consisted of three VIII grade students who were identified according to the categories of high, medium, and low mathematical ability. The main instruments were PISA-like math problem and interview guidelines based on metacognitive indicators. Data were obtained using written assessments and comprehensive interviews, then examined through qualitative descriptive analysis. The results showed that all students, regardless of mathematics ability level, made metacognitive errors. The most dominant errors occurred at the planning and evaluation stages. Students with low ability had difficulty understanding the problem, identifying relevant information, and designing a solution strategy. While students with medium and high abilities tend not to evaluate steps and results optimally. The results underscore the significance of enharing metacognitive abilities in mathematics education to foster reflective thinking and tackle complex problems.